(untitled) (Research, Society and Development, 2021)
Knowing the anthropometric profile of the elderly becomes important in multiprofessional health intervention, contributing to the reduction of morbidity and mortality rates, control and prevention of diseases associated with obesity. This study aims to describe the anthropometric profile of elderly people assisted by primary health care in Caicó. It is a pilot study, characterized as individual, observational and cross-sectional. Data were collected in Basic Health Units in Caicó from March to April 2020. In this study, 30 individuals aged 60 years or more participated, most of them female. Among the anthropometric variables presented by the sample are height, body weight, waist and hip circumference, body mass index and waist-hip ratio. The results of this research show the height varying between 1.33 and 1.70m; body weight between 36 and 91.7kg; waist circumference between 62 and 118 cm; hip circumference between 80 and 125 cm; the body mass index showed that 40% of the elderly are eutrophic, 40% are overweight and 20% are underweight; as for the waist-hip ratio, it was observed that in females there is a predominance of high risk, while in males a predominance of medium risk. The findings point to a tendency towards overweight, where most elderly people are above the anthropometric parameters recommended by the main health agencies, and that these data may contribute to the planning of strategies that can serve as a guide for interventions by multidisciplinary health teams that work in primary health care.